Effect of non-rubber components on the wear behavior of vulcanized natural rubber nanocomposites. (March 2023) - Chen, Xiangfei; Wang, Mengyu; Kong, Yiran; Li, Zhouxian; Wang, Rui; Huang, Yajiang; Li, Guangxian
Abstract: Non-rubber components (NRCs) in natural rubber (NR) endow NR with improved comprehensive properties. However, knowledge about their key roles in regulating the wear resistance of NR/carbon black (CB) nanocomposites is still lacking. In this study, two kinds of raw rubber with high and low NRCs contents were prepared from rubber latex, and then two corresponding vulcanizates were prepared by internal mixing. It was found that NRCs accelerated the curing rate and improved the mechanical properties of NR nanocomposites. More importantly, NRCs facilitated the formation of oily films during wear and improved largely the wear resistance. This enhanced resistance to wear was also attributed to the suppression of friction-induced heating and improved resistance against thermo-oxidative aging, which led to lower damage to the crosslinked network. Graphical Abstract: ga1 Highlights: Non-rubber components (NRCs) improved the wear resistance of natural rubber. NRCs promoted the formation of degraded oily films and reduced heat generation. NRCs reduced the damage to the crosslinked network due to thermal oxidation.